Effects of Palm Kernel Cake and Onggok Fermented by Aspergillus niger on Broiler Carcasses - Nurhayati, Nurhayati (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2008)
The experiment was conducted to evaluate the effects of the different crude protein and crude fiber content caused by usage level of palm kernel cake (PKC) and onggok (cassava byproduct) fermented by Aspergillus niger in ration on carcass weight and its components (thighs and breast, giblet, and abdominal fat) of broiler. This research used 96 DOC broiler of Lohman Platinum MB202. The chicken were reared in litter floor pen and was fed 0 (P0), 10 (P1), 20 (P2), and 30% (P3) of the fermented PKC-onggok mixture in the total ration. The broilers were reared for 6 weeks and fed ration and water ad libitum. The experiment was designed using a Completely Randomized Design with four ration treatments and four replications and each replication consisted of six chicken. Data were analyzed by analysis of variance, and continued with Duncan?s Multiple Range Test. The result showed that the different crude protein and crude fiber content caused by usage level of the fermented PKC-cassava byproduct mixture in broiler ration affected (P<0.05) weight of carcass, giblet, and abdominal fat, but did not affect (P>0.05) edible meat (thighs and breast). Carcass and its component on usage level of fermented PKC-cassava byproduct mixture until 30% in the ration was better than control. (Animal Production 10(1): 55-59 (2008) Key Words: Palm kernel cake, cassava byproduct, fermentation, carcass, broiler